Reduced ribosomes of the apicoplast and mitochondrion of Plasmodium spp. and predicted interactions with antibiotics. Issue 5 (May 2014) - Gupta, Ankit; Shah, Priyanka; Haider, Afreen; Gupta, Kirti; Siddiqi, Mohammad Imran; Ralph, Stuart A.; Habib, Saman
Abstract : Apicomplexan protists such as Plasmodium and Toxoplasma contain a mitochondrion and a relic plastid (apicoplast) that are sites of protein translation. Although there is emerging interest in the partitioning and function of translation factors that participate in apicoplast and mitochondrial peptide synthesis, the composition of organellar ribosomes remains to be elucidated. We carried out an analysis of the complement of core ribosomal protein subunits that are encoded by either the parasite organellar or nuclear genomes, accompanied by a survey of ribosome assembly factors for the apicoplast and mitochondrion. A cross-species comparison with other apicomplexan, algal and diatom species revealed compositional differences in apicomplexan organelle ribosomes and identified considerable reduction and divergence with ribosomes of bacteria or characterized organelle ribosomes from other organisms. We assembled structural models of sections of Plasmodium falciparum organellar ribosomes and predicted interactions with translation inhibitory antibiotics. Differences in predicted drug–ribosome interactions with some of the modelled structures suggested specificity of inhibition between the apicoplast and mitochondrion. Our results indicate that Plasmodium and Toxoplasma organellar ribosomes have a unique composition, resulting from the loss of several large and small subunit proteins accompanied by significant sequence and size divergences in parasite orthologues of ribosomal proteins.